ChemInform Abstract: Synthesis and Selective Inhibitory Activity Against Human COX‐1 of Novel 1‐(4‐Substituted‐thiazol‐2‐yl)‐3, 5‐di(hetero)aryl‐pyrazoline Derivatives. Issue 15 (25th March 2013) - Carradori, Simone; Secci, Daniela; Bolasco, Adriana; De Monte, Celeste; Yanez, Matilde
Abstract New pyrazoline derivatives (Vc), (Vd), (Vf)—(Vh) display promising inhibitory activities against human cyclooxygenase‐1 in the micromolar range, similar or better than the reference drugs indometacin and diclofenac.